ASSESSMENT OF HEAVY METAL CONCENTRATION IN COCONUT WATER - Aboni Afrose, MdDidarul Islam, Ashiqur Rahaman, (Recent Research in Science and Technology)
This study was based on determining concentration of essential and toxic heavy metal in coconut water available at a local Hazaribagh area in Dhaka, Bangladesh. All essential minerals, if present in the drinking water at high concentration or very low concentration, it has negative actions. In this study, fifteen samples and eight heavy metals were analyzed by Atomic Absorption Spectroscopy (AAS) method which was followed by wet ashing digestion method. The concentration obtained in mg/l were in the range of 0.3 to 1.5, 7.77 to 21.2, 0 to 0.71, 0 to 0.9, 0 to 0.2, 0.9 to 17.3, 0.1 to 0.9, 0 to 0.9 and 0 to 0.7 for Fe, Ni, Cu, Cd, Cr, Zn, Pb and Se respectively. From this data it was concluded that any toxic heavy metals like Cd, Cr, Pb and Ni exceed their toxicity level and some essential nutrients were in low concentration in those samples.